Protein Design - Guerois, Raphael.; Guerois, Raphael.; de la Paz, Manuela López.; de la Paz, Manuela López. (Methods in Molecular Biology,, 2006)
Recent major advances in our understanding of modulating protein functions has led to the development of new methods and algorithms to predict and decipher how amino acid sequences shape three-dimensional structures. Protein Design: Methods and Applications presents the most up-to-date protein design and engineering strategies so that readers can undertake their own projects with a maximum chance of success. The authors present integrated computational approaches that require various degrees of computational complexity, and the major accomplishments that have been achieved in the design and structural characterization of helical peptides and proteins. Other topics of discussion include: design of structural elementary motifs, entire proteins, and interfaces of protein complexes, and of amyloidogenic polypeptides and amyloid inhibitors. Authoritative and cutting-edge, Protein Design: Methods and Applications will be of major interest to protein scientists, biochemists, and all experimentalists selecting the strategy most adaptable for their design problem.